2012
DOI: 10.1002/jat.2838
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of effects of emodin in selected cancer cell lines: enhanced growth inhibition by ascorbic acid and regulation of LRP1 and AR under hypoxia‐like conditions

Abstract: This study explores the link between the antiproliferative activity of emodin through the generation of reactive oxygen species (ROS) in various cancer cell lines and the expression of the androgen receptor (AR) in the prostate cancer cell lines LNCaP (androgen-sensitive) and PC-3 (androgen-refractory), as well as the pro-metastatic low-density lipoprotein receptor-related protein 1 (LRP1) in the above prostate cancer cells and the nonprostate cell lines A549 (lung), HCT-15 (colon) and MG-63 (bone) under normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
(84 reference statements)
0
22
0
Order By: Relevance
“…Among many natural extracts, Emodin is one of compounds which is recognized as a drug candidate for cancer therapy. Previous reports have shown that Emodin inhibits cell growth in several types of cancer cells by regulating genes related to apoptosis, oncogenesis, proliferation and cancer cell invasion and metastasis [16, 17]. In this study, we examined Emodin and Dox effects to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many natural extracts, Emodin is one of compounds which is recognized as a drug candidate for cancer therapy. Previous reports have shown that Emodin inhibits cell growth in several types of cancer cells by regulating genes related to apoptosis, oncogenesis, proliferation and cancer cell invasion and metastasis [16, 17]. In this study, we examined Emodin and Dox effects to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin induces cell cycle arrest and apoptosis in cancer cells. According to previous reports [6, 7], Emodin has been proved to have good effects in preventing tumors, however, the effects and mechanism of Emodin on the chemoresistance have not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Emodin has also been found to exhibit cytotoxic effects against HepG2 cells (Yu, et al, 2013), the prostate cancer cell lines LNCaP and PC-3, the lung cancer cell line A549, the colon cancer cell line HCT-15, the bone cancer cell line MG-63 (Masaldan and Iyer, 2014) and the esophageal cancer cell lines EC-109 .…”
Section: Effect On the Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Furthermore, emodin decreased the association of AR and heat shock protein 90 and increased the association of AR and MDM2, which in turn induced AR degradation through proteasome-mediated pathway in a ligand-independent manner [60]. Emodin down-regulated AR in LNCaP under normoxic and hypoxia-like conditions (simulated by CoCl 2 and low-density lipoprotein receptor-related protein 1 (LRP1) under normoxia [61]. Similarly, Yu et al [43] showed that in LNCaP cells emodin reduces the expression and function of AR and enhances the expression of p53 and p21.…”
Section: Pancreatitismentioning
confidence: 99%